Pemanfaatan Pupuk Bioslurry Luaran Digester Biogas sebagai Pupuk Organik Tanaman Buah dalam Pot (Tabulampot) - Sri Ismiyati Damayanti; Dewi Agustina Iryani; Joni Agustian; Lilis Hermida; Amelia Yuliana Putri; Nurana; Yolanda Nur Sendy; Arlin Aprilia Saputri (Nemui Nyimah, 2026)
Fruit is an important source of essential vitamins and minerals required to maintain human health. However, the relatively high cost of fruit often limits access among rural communities, particularly those with low- to middle-income levels. One practical and sustainable approach to improving household fruit availability is the cultivation of fruit plants in pots (tabulampot), which can provide a continuous supply of fresh fruit while also enhancing the aesthetic value of home environments. In Kediri Village, the availability of bioslurry, an organic fertilizer generated as a by-product of biogas digesters, offers an additional advantage for tabulampot cultivation by reducing fertilizer costs and promoting environmentally friendly agricultural practices. This community service program aimed to: (1) increase public awareness of the importance of daily fruit consumption, (2) disseminate knowledge and appropriate technology related to tabulampot cultivation, and (3) promote the utilization of bioslurry as an organic fertilizer. The program was implemented through community outreach, practical training sessions, and continuous mentoring until the plants reached the fruiting stage. The results demonstrated that the program was successfully implemented with active participation and strong enthusiasm from community members. Participants contributed labor, gardening equipment, and logistical support throughout the activities. Student involvement also provided valuable opportunities for experiential learning, knowledge transfer, community engagement, and the development of social awareness. The program outputs included the establishment of fruit and vegetable plants as pilot demonstrations for bioslurry application, the preparation of technical and financial reports, and the development of scientific manuscripts for publication. Overall, the program enhanced community capacity in sustainable fruit cultivation and promoted the productive utilization of locally available organic resources.